Heavy metal accumulation in the sediments of the littoral zone of a deep alkaline lake - Caglar, Metin (Parlar Scientific Publications, 2015)
Lake Hazar is the second deepest lake in Turkey with a maximum depth of 210 m. The lake is significant due to its ecological and recreational value, as well as fisheries. Concentrations of various heavy metals (Cu, Cd, Co, Cr, Fe, Mn, Ni, Pb and Zn) were analyzed in the bottom sediments collected from different depths (2, 4, 6, 8, 10, 15 and 20 m) of the littoral zone around the lake in order to determine the degree of heavy metal accumulation in Lake Hazar. Of all metals, Fe was found to be have the highest concentration in the sediment samples, followed by Mn. However, the concentrations of Co and Pb were under detectable levels. Concentrations of all heavy metals varied depending on the depth and direction of the littoral zone of the lake. However, there was a weak correlation between heavy metal accumulation and depth. Most of the littoral region of Lake Hazar appeared to be either unpolluted or slightly polluted with heavy metals, with the exception of Fe, the only metal which was found to have accumulated in dangerous concentrations in the sediments. The difference between depths, directions and the variables was found statistically insignificant (P>0.05). © by PSP.
Keywords: Accumulation; Heavy metal; Lake Hazar; Sediment; Turkey